Ignore the Poets at Your Peril: A Reflection on Neither Settler nor Native; The Making and Unmaking of Permanent Minorities. Issue 1 (2nd January 2022) - Troutt Powell, Eve M.
Abstract: Mahmood Mamdani has posited a new approach to decolonization and to the question of extreme violence meted out in decades of independence, the age of political modernity. To do so, he explores the issues of justice and accountability in five case studies: Native Americans in the United States; the Nuremberg trials in Germany; South Africa and apartheid; South Sudan; and Israel/Palestine. Do his ideas offer his readers something really new? This review questions the historical methodologies used by Mamdani, a political theorist, and explores different artistic origins for people in these countries who have long articulated the lived experience between "settler" and "native."